From your house to their House? Representation, political rhetoric and housing markets - Ansell, B; Bokobza, L; Nyrup, J (2022)
In the last decades, advanced industrial democracies have seen a rapid, yet unequal, surge in housing prices. While scholars have examined whether house prices shape the political behaviour of voters, we know little about how they change politicians’ stances on housing policy. We rely on innovative text analysis methods on all parliamentary speeches on housing since 1997 in the UK and identify three main policy issues: housing supply, housing demand, and welfare-related concerns. The analysis shows that higher housing prices in an MP’s con- stituency are associated with more expressed concern about housing demand and housing wel- fare support, particularly for Labour MPs relative to Tory MPs. Furthermore, we find that MPs from all parties talk more about housing supply in constituencies with higher housing prices. This provides new insights into the determinants of political elites’ attitudes regarding welfare and show that MPs react to changes in their constituents living conditions.